The influence of helium-induced defects on the migration of strontium implanted into SiC above critical amorphization temperature - Mokgadi, T. F.; Abdalla, Z. A. Y.; Madhuku, M.; Njoroge, E. G.; Mlambo, M.; Mdluli, P.; Sohatsky, A.; Skuratov, V. A.; Malherbe, J. B.; Hlatshwayo, T. T. (Frontiers in Materials, 2023)
The presence of radiation-induced defects and the high temperature of implantation are breeding grounds for helium (He) to accumulate and form He-induced defects (bubbles, blisters, craters, and cavities) in silicon carbide (SiC). In this work, the influence of He-induced defects on the migration of strontium (Sr) implanted into SiC was investigated. Sr-ions of 360 keV were implanted into polycrystalline SiC to a fluence of 2 × 1016 Sr-ions/cm2 at 600°C (Sr-SiC). Some of the Sr-SiC samples were then co-implanted with He-ions of 21.5 keV to a fluence of 1 × 1017 He-ions/cm2 at 350°C (Sr + He-SiC). The Sr-SiC and Sr + He-SiC samples were annealed for 5 h at 1,000°C. The as-implanted and annealed samples were characterized by Raman spectroscopy, scanning electron microscopy (SEM), atomic force microscopy (AFM), transmission electron microscopy (TEM), and Rutherford backscattered spectrometry (RBS). Implantation of Sr retained some defects in SiC, while co-implantation of He resulted in the formation of He-bubbles, blisters, and craters (exfoliated blisters). Blisters close to the critical height and size were the first to exfoliate after annealing. He-bubbles grew larger after annealing owing to the capture of more vacancies. In the co-implanted samples, Sr was located in three regions: the crystalline region (near the surface), the bubble region (where the projected range of Sr was located), and the damage region toward the bulk. Annealing the Sr + He-SiC caused the migration of Sr towards the bulk, while no migration was observed in the Sr-SiC samples. The migration was governed by “vacancy migration driven by strain fileds.”